Principal Leadership In an Effort to Improve Student Entrepreneurship Competence - Engkus Kuswarno; Ibrahim Danuwikarsa; Faiz Karim Fatkhullah; Roli Fola Cahya Hartawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the low entrepreneurial competence of vocational students, so that it has an impact on the lack of vocational graduates who open new jobs. The approach in this study is descriptive qualitative, so the purpose of this study is to describe and analyze 1) the leadership characteristics of the principals of SMKN 1 and SMKN 4 Metro Lampung, 2) the principal's leadership strategy which includes the application of environmental analysis. , strategy formulation, strategy implementation and strategy evaluation, 3) Excellent entrepreneurship program. SMKN, 4) the obstacles faced, and 5) solutions to overcome these problems. The results of the study: 1) The principal of SMKN implements transformational leadership 2) The principal has implemented a strategy to improve the quality of graduates but has not yet been formulated in the school's RKS/RKAS. 3) The implementation of entrepreneurship programs in SMKN has been integrated with very high and entrenched education and entrepreneurial values ​​in schools. 4) There are several obstacles for the principal in an effort to improve the entrepreneurial competence of students. 5) There is a solution to overcome the obstacles for the Principal in an effort to improve the entrepreneurial competence of students